Shifting the Stories around Academic Integrity: How Critically Reflective Educators Create Empowered Student Learning - Barr, Lauren (Canadian Perspectives on Academic Integrity, 2021)
Research shows that the underlying attitudes of educators not only influence instruction but also impact student outcomes themselves. As we begin to reflect on what the past year has taught us, we want to consider how we as educators can challenge our own attitudes around academic misconduct and empower our students to take ownership of their education. In this session, we will look at the ways in which your inherent biases about student integrity could be surfacing in your online and onboard classroom. We will consider practical shifts in the way you teach and provide feedback in order to influence student outcomes in meaningful ways. You will leave this session with applied evidence-based ideas for improved learning design by incorporating some of Turnitin’s new capabilities into the assessment workflow.